2020
DOI: 10.1002/nop2.544
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' perceptions of patient participation in the myocardial infarction pathway

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…This will help correct patients' misconceptions, guide them to vent their bad emotions reasonably, and assist patients to establish correct healthy behaviors, making full use of family and social support and quickly accepting the patients' role and the influence of formal illness and surgery on themselves. Thus, this effectively alleviates people's sense of psychological crisis and bad psychological emotions [Silber 2017;Bårdsgjerde 2020]. In this study, the scores of quality of life and hope level in the intervention group were higher than those in the control group after 4 weeks intervention (P < .05).…”
Section: Discussionmentioning
confidence: 54%
“…This will help correct patients' misconceptions, guide them to vent their bad emotions reasonably, and assist patients to establish correct healthy behaviors, making full use of family and social support and quickly accepting the patients' role and the influence of formal illness and surgery on themselves. Thus, this effectively alleviates people's sense of psychological crisis and bad psychological emotions [Silber 2017;Bårdsgjerde 2020]. In this study, the scores of quality of life and hope level in the intervention group were higher than those in the control group after 4 weeks intervention (P < .05).…”
Section: Discussionmentioning
confidence: 54%
“…The assessment of the methodological quality of the included studies is displayed in Additional file 1 : Appendix 4. All included qualitative studies indicated congruity between the research methodology and the research question or objectives and utilized appropriate data collection methods and approach to data analysis [ 3 , 15 , 26 31 ]. The cultural or theoretical perspective in relation to the research was discussed in three studies [ 26 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Scores of 4 or 5 out of five suggest a high level of dependability, while scores of 2 or 3 suggest a moderate level of dependability. In this review, seven studies [ 3 , 15 , 26 30 ] were assessed as having a high level of dependability and one study [ 31 ] a moderate level of dependability. Credibility was established by assessing the congruency between the author’s interpretation and supporting data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rehabilitation exercises will not cause complications due to increased physical activity, and instead they prevent the multiple complications that can be caused by prolonged bed rest. The 7-day gradual early functional exercise program is based on the characteristics of sports metabolism in the young and middle-aged population, and includes specially devised scientific rehabilitation exercises to improve the body's anti-thrombotic ability, accelerate vascular remodeling, and reduce the incidence of postoperative angina, arrhythmia, and other complications (23,24).…”
Section: Discussionmentioning
confidence: 99%